2014
DOI: 10.1530/rep-14-0149
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of advanced glycation end products in the rabbit blastocyst under maternal diabetes

Abstract: Diabetes mellitus (DM) during pregnancy is one of the leading causes of perinatal morbidity and birth defects. The mechanism by which maternal hyperglycemia, the major teratogenic factor, induces embryonic malformations remains unclear. Advanced glycation end products (AGEs) are known to accumulate during the course of DM and contribute to the development of diabetic complications. Employing a diabetic rabbit model, we investigated the influence of maternal hyperglycemia during the preimplantation period on AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Furthermore, sorbitol and fructose may also glycate nitrogens on proteins, such as collagen, producing advanced glycation end products (AGEs), like carboxymethyllysine (CML) and pentosidine [32]. We have recently shown that the total amount of AGEs was increased and that the level of CML was especially elevated in blastocysts from diabetic rabbits [33]. The metabolome analysis confirmed that N6-CML increased in plasma from diabetic rabbits.…”
Section: Maternal Diabetes Mellitus Increases Glycolysis and Pentose mentioning
confidence: 84%
“…Furthermore, sorbitol and fructose may also glycate nitrogens on proteins, such as collagen, producing advanced glycation end products (AGEs), like carboxymethyllysine (CML) and pentosidine [32]. We have recently shown that the total amount of AGEs was increased and that the level of CML was especially elevated in blastocysts from diabetic rabbits [33]. The metabolome analysis confirmed that N6-CML increased in plasma from diabetic rabbits.…”
Section: Maternal Diabetes Mellitus Increases Glycolysis and Pentose mentioning
confidence: 84%
“…In addition, AGEs have been implicated in the pathogenesis of infertility. As a consequence of type 1 diabetes mellitus in rabbits, high amounts of AGEs accumulated in the endometrium, follicular fluid, oocytes, and blastocysts . In human‐assisted reproductive technology, Jinno et al reported that AGEs accumulation in follicular fluid and serum negatively correlated with follicular growth, fertilization, and embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Excess glucose also induces an inflammatory reaction, possibly because of increased advanced glycation end products (Haucke et al 2014) and activation of hexosamine pathways, in particular O-linked glycosylation (Pantaleon et al 2010, Pantaleon 2015, Wong et al 2015. Other pathways that are activated include protein kinase C signalling and extracellular matrix remodelling into the fibrotic-like phenotype.…”
Section: Response To Energetic Stressmentioning
confidence: 99%